Peran Pendidikan Islam dalam Pengembangan Potensi Siswa di Sekolah Dasar - Shifa Laelatul Khusnia; Najwa Zakiyatiz Zulfa; Rabbani Zulfan Mumtaz (Al-Kindi, 2026)
This study aims to analyze the understanding of human beings and the development of their potential from an Islamic perspective. The methodology applied is qualitative research with a literature study approach, which involves reviewing various sources such as books and academic journals related to the research topic. The findings of this study reveal that in Islam, humans are viewed as servants of Allah (abdullah) and as leaders on earth, who bear moral and social responsibilities. Humans also possess innate potential (fitrah), which includes physical, intellectual, emotional, and spiritual aspects. These potentials need to be developed through Islamic education that is comprehensive and integrated in order to achieve a balance between worldly and hereafter life. In other words, the goal of developing human potential in Islam is to produce well-rounded individuals who are faithful, knowledgeable, and of good character. The implications of this research indicate that the development of students' potential can be done through integrative Islamic Religious Education learning by paying attention to cognitive, affective, and psychomotor aspects in elementary schools.